Pengujian Formil Peraturan Antara Indonesia dan Kolombia - Firmansyah, Adithya Tri; Aritonang, Syofina Dwi Putri; Pritasari, Amalia Zulfa; Zulmi, Muhammad Nizar; Alivia, Imera Azzahra (Widya Yuridika, 2024)
The authority to review laws by the Constitutional Court is manifested in 2 (two) forms, namely material testing and formal testing. However, since the existence of the Constitutional Court, only 1 (one) application has been granted by the Constitutional Court, namely a request for a formal review of the Job Creation Law. Even then, it was only partially granted. The existence of this fact certainly shows that the role of the Constitutional Court has not been optimal. Therefore, this research aims to outline the prescription of the need to optimize the role of the Constitutional Court in the formal review of laws. This research uses normative (legal) research typology. The results of this study conclude: First, the role of the Constitutional Court in the formal review of laws can still be said to be not optimal because the Constitutional Court itself is still very limited in canceling laws, as evidenced in Decision Number 91 / PUU-XVIII / 2020, the Constitutional Court tends to compromise with the language of conditional unconstitutional decisions in deciding applications for formal testing of the Job Creation Law. Second, the countries of Colombia and Indonesia show that the practice of formal testing of the Law by the Constitutional Court is something that needs to be done if there is a violation of the formation procedure by the legislator, it is just that the Colombian Constitutional Court in conducting formal testing takes a more progressive step, this is indicated by the quality and quantity of handling of formal test cases decided, on the other hand in Indonesia, the Constitutional Court seems to take a position that tends to be very limited in conducting formal testing, it even looks unfamiliar to do so, besides that the 1945 Constitution also does not provide rigid arrangements regarding the basis for formal testing of laws by the Constitutional Court.